Based on the Primary and Secondary School Teachers TPACK Informationization Teaching Ability Ascension Path to Explore - Liu, Shasha; Guo, Haixi (Transactions on Social Science, Education and Humanities Research, 2023)
Under the current situation, how to improve teachers' level of information technology, to improve the level of teachers' information technology has a very important role. Therefore, in the process of teachers' information technology education, carries on the thorough theoretical analysis and practical exploration, has the very vital significance. TPACK framework teachers information technology teaching, based on the ability of interpretation theory, combined with the effect and influence of information literacy in the whole teaching process, from the information technology teaching design ability, the informationization teaching ability, information, information integration ability to teach students to learn the evaluation ability, informationization teaching research ability five aspects to explore the connotation of the theory of primary and secondary school teachers' information technology teaching ability and knowledge can deconstruct changes, and put forward the planning guide promote informatization instructional design ability, and dig dug the informationization teaching conformity ability. Assignment of smelting technology can improve the informationization teaching ability and multi-dimensional teaching evaluation ability, improve the information science and education integration to strengthen information countermeasures and suggestions of teaching research ability, to explore the new era of university teachers' information technology teaching ability of optimization path to provide theoretical reference.